Keterlibatan Orang Tua dan Kesiapan Siswa Sekolah Dasar Negeri di Sidoarjo - Ummah, Nuril Maghfirotil; Mariyati, Lely Ika (Web of Scientist International Scientific Research Journal, 2024)
This research is motivated by the phenomenon of low readiness of students to enter elementary school in grade 1 students of SD Negeri Sidokare 2 Sidoarjo. This study aims to determine the relationship between parental involvement and children's readiness to enter elementary school in grade 1 SD Negeri Sidokare 2 Sidoarjo. This type of research is correlational quantitative. The variables in this study are parental involvement as the independent variable and children's readiness to enter elementary school as the dependent variable. The population of this research is 66 students. The sampling technique used is non-probability sampling, namely saturated sampling. Data were collected using a psychological scale with the Likert scale model and the NST test kit, namely the parental involvement scale and the NST test kit for children's readiness to enter elementary school. Analysis of the data in this study used the Pearson Product Moment correlation technique with the help of the SPSS 26.0 for windows program. The results of the correlation analysis obtained a correlation coefficient of rxy = 0.461 (significance 0.000 <0.05) meaning that the research hypothesis was accepted, namely that there was a significant positive relationship between the variable parental involvement and the variable readiness of children to enter elementary school in grade 1 SD Negeri Sidokare 2 Sidoarjo.